Post-Exercise Supplementation: Impact on VO₂Max of Futsal Athletes - Ittaqwa; Vai, Aref (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
Background: Futsal is a high-intensity sport that requires optimal lung capacity and aerobic endurance, efforts to improve VO₂max are often associated with nutritional interventions, including supplementation. Calcium D Redoxon (CDR), which contains vitamin C, vitamin D, and calcium, energy metabolism, and the immune system. This study aims to investigate the effect of Calcium D Redoxon supplementation after exercise on the improvement of VO₂max in futsal athlete. Methods: The research method eksperimen used a design one-group pretest-posttest design with a total sampling technique involving 21 athletes. The instrument for measuring VO₂max endurance was a respirometer (FEV1), and data analysis included normality tests and a t-test. Result: The normality test results showed that variable X had an Asymp. Sig. (2-tailed) value of 0.103 (p > 0.05) and variable Y had an Asymp. Sig. (2-tailed) value of 0.148 (p > 0.05), indicating that both datasets were normally distributed. Based on the t-test results, the pretest mean was 4492.952 ml with a t-value of 43.418 and a significance value of 0.000 (p < 0.05), indicating statistical significance. The posttest mean was 4088.857 ml with a t-value of 42.525 and a significance value of 0.000, also indicating high statistical significance. Although both results are statistically significant, there was an average decrease of 404.095 ml from pretest to posttest. Conclusion: These findings indicate that the intervention did not positively impact lung capacity improvement; in fact, it tended to cause a decrease.